2019
DOI: 10.1002/ajh.25641
|View full text |Cite
|
Sign up to set email alerts
|

Stability and uniqueness of clonal immunoglobulin CDR3 sequences for MRD tracking in multiple myeloma

Abstract: Minimal residual disease (MRD) tracking, by next generation sequencing of immunoglobulin sequences, is moving towards clinical implementation in multiple myeloma.However, there is only sparse information available to address whether clonal sequences remain stable for tracking over time, and to what extent light chain sequences are sufficiently unique for tracking. Here, we analyzed immunoglobulin repertoires from 905 plasma cell myeloma and healthy control samples, focusing on the third complementarity determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 37 publications
8
37
0
Order By: Relevance
“…There are very few studies addressing the serial assessment of MRD in MM, although this strategy has been successfully used in other diseases, such as lymphoma or leukemia, [18][19][20] even knowing the stability of VDJ along the natural history of MM. 21 Here, we have demonstrated that MRD monitoring by NGS is feasible and provides reproducible data, as shown in Figure 2B.…”
Section: Discussionsupporting
confidence: 52%
“…There are very few studies addressing the serial assessment of MRD in MM, although this strategy has been successfully used in other diseases, such as lymphoma or leukemia, [18][19][20] even knowing the stability of VDJ along the natural history of MM. 21 Here, we have demonstrated that MRD monitoring by NGS is feasible and provides reproducible data, as shown in Figure 2B.…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, the CDR3 sequences were identical across sample pairs in all patients. Highly conserved CDR3 sequences over time in MM is consistent with previous studies 33 , including CDR3 reconstruction from RNA sequencing of sequential samples in the CoMMpass cohort 34 .…”
Section: Resultssupporting
confidence: 89%
“…1,000,000 0 10,000,000 20,000,000 30,000,000 40,000,000 50,000,000 60,000,000 70,000,000 80,000,000 90,000,000 100,000,000 110,000,000 120,000,000 130,000,000 140,000,000 150,000,000 160,000,000 170,000,000 180,000,000 190,000,000 Highly conserved CDR3 sequences over time in MM is consistent with previous studies 33 , including CDR3 reconstruction from RNA sequencing of sequential samples in the CoMMpass cohort 34 .…”
Section: Resultssupporting
confidence: 88%